1999
DOI: 10.1007/s00585-999-0613-4
|View full text |Cite
|
Sign up to set email alerts
|

Nongyrotropic particle distributions in space plasmas

Abstract: Abstract. In nonstationary, strong inhomogeneous or open plasmas particle orbits are rather complicated. If the nonstationary time scale is smaller than the gyration period, if the inhomogeneity scale is smaller than the gyration radius, i.e. at magnetic plasma boundaries, or if the plasma has sources and sinks in phase space, then nongyrotropic distribution functions occur. The stability of such plasma con®gurations is studied in the framework of linear dispersion theory. In an open plasma nongyrotropy drives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…It is important to point out that in certain parameter regimes other that what is considered here, the introduction of a nongyrotropic plasma distribution by itself can generate an instability when the corresponding gyrotropic situation is stable. This is true for both stationary [ Brinca and Romeiras , 1998; Brinca et al , 1998; Brinca , 1999; Motschmann and Glassmeier , 1998; Motschmann et al , 1999] and time‐varying [ Motschmann et al , 1999] nongyrotropic distributions.…”
Section: Results Of Hybrid Simulationsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is important to point out that in certain parameter regimes other that what is considered here, the introduction of a nongyrotropic plasma distribution by itself can generate an instability when the corresponding gyrotropic situation is stable. This is true for both stationary [ Brinca and Romeiras , 1998; Brinca et al , 1998; Brinca , 1999; Motschmann and Glassmeier , 1998; Motschmann et al , 1999] and time‐varying [ Motschmann et al , 1999] nongyrotropic distributions.…”
Section: Results Of Hybrid Simulationsmentioning
confidence: 94%
“…Similar conclusions were made on the basis of linear stability studies by Brinca and Romeiras [1998]and Brinca [1999], who showed that in certain parameter regimes, parallel propagating waves are stable in the presence of time‐varying nongyrotropic distributions, unless a finite perpendicular current exists. Motschmann et al [1999] found that a time‐varying nongyrotropic plasma is linearly stable to parallel propagating waves, for certain parameters, unless an additional energy contribution such as a temperature anisotropy is present. Motschmann et al [1999] also states that nongyrotropic distributions are expected to be stable when both the perpendicular and parallel velocities are conserved and particle diffusion occurs along the gyrophase angle only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We noted at the beginning of section 4 that the reflected protons are not gyrotropic as we assume in the quasilinear analysis, since their motion is coherent in gyrophase. However, Motschmann et al [1999] investigated the stability of a nongyrotropic ion distribution and concluded that the gradients in gyrophase do not introduce new strong instabilities to compete with that which we consider here.…”
Section: Discussionmentioning
confidence: 94%